What Is Asked in Clinical Data Request Forms? A Multi-site Thematic Analysis of Forms Towards Better Data Access Support - Hanauer, David A (AMIA Annu Symp Proc, 2014)
Many academic medical centers have aggregated data from multiple clinical systems into centralized repositories. These repositories can then be queried by skilled data analysts who act as intermediaries between the data stores and the research teams. To obtain data, researchers are often expected to complete a data request form. Such forms are meant to support record-keeping and, most importantly, provide a means for conveying complex data needs in a clear and understandable manner. Yet little is known about how data request forms are constructed and how effective they are likely to be. We conducted a content analysis of ten data request forms from CTSA-supported institutions. We found that most of the forms over-emphasized the collection of metadata that were not considered germane to the actual data needs. Based on our findings, we provide recommendations to improve the quality of data request forms in support of clinical and translational research.